Comparison of the anaerobic power of Brazilian professional football players grouped by tactical position - Cruz dos Santos, R. R.; Victor de Sousa, C.; Reis Olher, R.; Vieira de Sousa Neto, I.; Alves Pereira, L.; Magalhaes Sales, M. (Montenegrin Journal of Sports Science and Medicine, 2014)
Football is characterized as a predominately aerobic modality, however, during a match; the most important actions performed by the players are in short duration and high intensity. In addition, this sport presents to have some particularities, such as, highlights differences of each tactical position. Thus, this study aimed to compare the anaerobic power of professional football players grouped by different tactical positions. Thirty professional football players separated in three groups, goal¬keep¬ers+fullbacks, sideways+DMF (defensive middlefields) and OMF (offensive middlefields)+forwards, performed two anaerobic po¬wer tests, Running anaerobic sprint test and Sargent jump test Goalkeepers+fullbacks showed higher values of body mass index and absolute anaerobic power (w), using Sargent jump test than the others, but when analyzed the RAST results, this same group presented lower values (p<0.05) of relative AP (w·kg-1). OMF+forwards showed to have the best Pmed and Pmax values (p<0.05), when compared with defensive players. These results suggest the use of running anaerobic sprint test and sargent jump test together when is proposed to measure the anaerobic power of football players, and also a anthropometric evaluation, so the training can be more specific e efficient to each tactical position and athlete.